Pengaruh Independensi Dewan Direksi, Struktur Kepemilikan Perusahaan dan Koneksi Politik Perusahaan terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan - Anita Anita; Suryani Suryani (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
This study aims to examine the effect of the board of directors structure and ownership structure to corporate social responsibility disclosure in companies listed on the Indonesia Stock Exchange period 2015-2019 and examine the association of corporate political relations with the level of corporate social responsibility disclosure to determine how the relationship between the state and the corporate sector affects CSR engagement. The results showed that there was no significant relationship between board of directors structure, ownership structure, corporate political connections to the level of corporate social responsibility disclosure. This research empirically shows that managers, investors, political members and other stakeholders will not influence the corporate social responsibility disclosure in the annual report